-2x-6=-6x+-2

Simple and best practice solution for -2x-6=-6x+-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x-6=-6x+-2 equation:


Simplifying
-2x + -6 = -6x + -2

Reorder the terms:
-6 + -2x = -6x + -2

Reorder the terms:
-6 + -2x = -2 + -6x

Solving
-6 + -2x = -2 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-6 + -2x + 6x = -2 + -6x + 6x

Combine like terms: -2x + 6x = 4x
-6 + 4x = -2 + -6x + 6x

Combine like terms: -6x + 6x = 0
-6 + 4x = -2 + 0
-6 + 4x = -2

Add '6' to each side of the equation.
-6 + 6 + 4x = -2 + 6

Combine like terms: -6 + 6 = 0
0 + 4x = -2 + 6
4x = -2 + 6

Combine like terms: -2 + 6 = 4
4x = 4

Divide each side by '4'.
x = 1

Simplifying
x = 1

See similar equations:

| 3(4x-2)=9+2x+5 | | 3-q/4=18 | | 3a-12= | | 130/n=65/100 | | 3x+4=51 | | 12x-18=36-15x | | ln(x+4)-ln(x-5)=3 | | a(7b-2c)= | | 4x+10y=3000 | | 250x^2-90=0 | | 3.14+y=2 | | 5a+5b+5c= | | 4(2a-b)= | | f(-8)=36x+9x-7 | | a=23+4 | | 8x-25=3x-5 | | 4(3b-2a)= | | 13k+24=6k+6 | | f(-1)=25x-5x | | 5x+15=28x | | (17w-13)+(-6w+7)= | | .28x=700 | | x=-1.25y+3 | | 4.1x-17.49=2.6 | | (7w-13)+(-6w-7)= | | x-3=-1.25y | | f(-1)=4x-2x | | t+8t= | | f(2)=16x-2x | | 6x^2-84x+160=0 | | Y=-0.6(3)+0 | | 3sin^2x-3sinx-2=0 |

Equations solver categories